2007
DOI: 10.1107/s1744309107000474
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and X-ray diffraction analysis of the DNA-remodelling protein DnaD fromBacillus subtilis

Abstract: The DnaD protein is an essential component of the chromosome-replication machinery of the Gram-positive bacterium Bacillus subtilis and is part of the primosomal cascade that ultimately loads the replicative ring helicase DnaC onto DNA. Moreover, DnaD is a global regulator of DNA architecture, as it forms higher order nucleoprotein structures in order to open supercoiled DNA. Here, the crystallization and preliminary X-ray diffraction analysis of the two domains of DnaD from B. subtilis are reported. Crystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Crystallization of the native DnaD Nd was carried out as described before 44. For obtaining phase information, samples of the DnaD Nd were prepared in the presence of selenomethionine (SeMet) by transforming the expression plasmid in methionine auxotroph E. coli B834 (DE3) cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystallization of the native DnaD Nd was carried out as described before 44. For obtaining phase information, samples of the DnaD Nd were prepared in the presence of selenomethionine (SeMet) by transforming the expression plasmid in methionine auxotroph E. coli B834 (DE3) cells.…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression was then induced by adding isopropyl-β- d -thioga-lactopyranoside to a final concentration of 1 mM, and cultures were further grown overnight. Purification and crystallization of SeMet Nd were carried out as described for the native protein but at the lower protein concentration of 10 mg mL −1 , in contrast to 20 mg mL −1 for the unlabeled protein 44…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the N-terminal domain of B. subtilis DnaD has been determined by X-ray crystallography ( 16 , 28 , 29 ), revealing a winged helix-turn-helix fold. Whilst proteins with such a motif commonly, but not exclusively, have a DNA-binding function, this is not the case for the DnaD N-terminal domain, which instead facilitates formation of extensive protein scaffolds ( 14–16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nd is responsible for scaffold formation in the absence of DNA, while Cd binds to DNA and oligomerizes 18. Both domains have been crystallized and structural determination is underway 28. Topoisomerase I-based assays revealed that full-length DnaD or Cd binding to DNA induces untwisting of the duplex, thus converting it from plectonemic to paranemic 19.…”
Section: Introductionmentioning
confidence: 99%